Principles, moral and positivism: answers and redefinition of contemporary positivism (2014)
The origin of the contemporary theory of the principles is trying to overthrow the positivism of Ronald Dworkin. In this paper is intended to outline the positivist argument against Dworkinian rest of morality of law. Briefly outlines the exclusive and inclusive responses. Are these answers, which eventually redefine the contemporary character of legal positivism.